Investigations to determine an optimal medium for callus initiation on stem explants of Prunus salicina Lindl. cv. Harry Pickstone - Thomas, C.(Chantall) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1986.